VARIASI PERTUMBUHAN DAN PARAMETER GENETIK PADA TIGA PLOT UJI KETURUNAN NYAWAI (Ficus variegata Blume) DI BANTUL - Liliek Haryjanto; Prastyono Prastyono; Vivi Yuskianti (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2014)
Three progeny trials of nyawai (Ficus variegata Blume) were established in Mangunan, Bantul, Yogyakarta. The trials were grouped in three sublines based on their original provenances: Lombok, Banyuwangi and Cilacap-Pangandaran. Each subline was laid out in Randomized Completely Block Design (RCBD) comprising 15-19 families.This study was aimed to observe growth variation and genetic parameter of the three sublines progeny trial at six and twelve months after planting. Analysis of variance was made to observe family effect for height and diameter, then the component of variance of each trait was used to estimate the heritability and genetic correlation. The results of study showed that at 12 months of age the survival rate of the trial was more than 90%, indicating high adaptability of the species to the trial site. Family effect on growth traits tended to increase as the trees getting older. Except for diameter in sub-line of Banyuwangi, estimation of individual heritabilities for height and diameter traits ranged from 0.015 to 0.241 and 0.017 to 0.096 respectively, with the corresponding for family heritabilities of height and diameter traits ranged from 0.09 to 0.434 and 0.123 to 0.352 respectively. It suggests that genetic control of the traits at both individual and family level were weak in the early growth. Genetic correlation between the two growth traits were varied among the sub-lines, indicating the character and growth pattern of nyawai seemed to be different among the sub-lines.